Medical specialist distributions in Ecuador: a geographical and temporal analysis of data from 2000 to 2017 - Alejandro Rodriguez; Adriana Romero-Sandoval; Bernardo A. Sandoval; Natalia Romero (BMC, 2022)
Abstract Background Knowledge of medical specialists' numbers and geographical distribution are essential for planning health services and health workforce supply. However, although the distribution of physicians is a significant concern for society and policymakers in Ecuador, no studies have evaluated the distribution of specialists in the country. This study aimed to explore the geographical and temporal distribution of medical specialists in Ecuador over 18 years from 2000 to 2017 and analyse its implications for health planning and medical training. Methods We conducted an ecological time-series study based on the National Statistical Register of Resources and Health Activities data. This register provides administrative information for health professionals working in public and private health institutions. Rates of medical specialists by year, geographical area, and speciality were estimated. We used joint-point analyses to identify time trends for medical specialists and physicians in training. Results From 2000 to 2017, medical specialists grew from 2737 to 10,929. The rate of medical specialists per 10,000 population increased from 4 in 2000 to 10.3 in 2017. Based on Joint point analysis, two temporal trends were identified. Between 2000 to 2015, specialists increased by 4.1% per year, and between 2015 and 2017, they increased by 20% per year. For the entire study period, three cities (Quito, Guayaquil, and Cuenca) accounted for more than 50% of the specialists in the country. However, medical specialists in other cities and rural areas increased from 37% in 2000 to 46% in 2017. The provinces of Esmeraldas, Carchi, Bolívar and Los Ríos presented rates of less than 6 specialists per 10,000 population by 2017. Of the 46 medical specialities identified by 2017, three represented more than 30% of the professionals (gynaecology 12%, paediatrics 11% and family and community health 8.4%). Conclusions This study shows that the number of medical specialists in Ecuador has increased significantly over the last two decades, although with inequalities in the distribution of specialists between provinces and regions. The results of this study provide background for the Ecuadorian health system when introducing Human Resources of Health (HRH) policies.